Activity Modification and Load Management of Adolescents With Patellofemoral Pain: A Prospective Intervention Study Including 151 Adolescents. Issue 7 (June 2019) - Rathleff, Michael Skovdal; Graven-Nielsen, Thomas; Hölmich, Per; Winiarski, Lukasz; Krommes, Kasper; Holden, Sinéad; Thorborg, Kristian
Background: Patellofemoral pain (PFP) affects 7% of adolescents, especially those who are highly active. Exercise-focused treatments show limited effect and overlook activity modification and load management. As many adolescents continue at high levels of sports despite pain, a new strategy addressing this problem is warranted. Purpose: To investigate the effects of a treatment strategy for adolescents that focuses on activity modification and load management. Study Design: Cohort study; Level of evidence, 2. Methods: Adolescents aged 10 to 14 years with PFP were included (N = 151). The 12-week intervention included 4 supervised sessions with a physical therapist, which adolescents and parents were required to attend. The intervention included activity modification (weeks 1-4) to reduce loading of the patellofemoral joint via an activity ladder and pain monitoring, home-based exercises (weeks 5-8), and return-to-sport guidance (weeks 9-12). Primary outcome was a 7-point global rating of change, ranging from "much improved" to "much worse." Adolescents were considered to have a successful outcome if they reported "much improved" or "improved." The primary endpoint was at 12 weeks, with additional follow-up at 4, 24, and 52 weeks. Secondary outcomes included the Knee injury and Osteoarthritis Outcome Score (KOOS), hip and knee torque, sports participation, satisfaction with treatment, and use of painkillers. Results: At 12 weeks, 87% completed the full questionnaire, of which 86% reported a successful outcome, as compared with 77% (95% CI, 68%-83%) at 6 months and 81% (95% CI, 73%-88%) at 12 months. There were large clinically relevant improvements in 3 KOOS subscales: Pain, Sport/Recreation, and Quality of Life (13-24 points). Hip and knee torque increased by 20% to 33%. In total, 68% were back playing sport after 3 months, which increased to 79% at 6 months and 81% at 12 months. The majority were satisfied with the treatment (90%) and would recommend it to a friend (95%). No specific patient characteristics were associated with prognosis. Conclusion: A treatment strategy focusing on activity modification and load management was associated with high rates of successful outcome among adolescents with PFP at 12 and 52 weeks. These short- and longer-term outcomes were supported by improvements in symptoms and objective measures of hip and knee torque. Registration: NCT02402673 (ClinicalTrials.gov identifier)